Tindakan Corrective Maintenance pada Penggantian Poros Elektro Motor yang Patah Akibat Beban Berlebih di Mesin Separator PT. Hutahaean - Karti, Karti; Nainggolan, Geo Peterson (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
This research discusses the replacement of a broken motor shaft due to overload as a Corrective Maintenance action on the separator unit at PT. Hutahaean, Tapioca Factory. The objective of this research is to understand the Standard Operating Procedure (SOP) for replacing a broken motor shaft and to apply preventive steps to avoid further damage to the electric motor in the separator unit. The electric motor plays a crucial role in driving the separator machine, especially in the separation process of tapioca starch. Overloading led to the breakage of the motor shaft, disrupting the production flow. This study demonstrates that effective Corrective Maintenance can restore the machine's optimal function and reduce production downtime. The findings also highlight the importance of routine maintenance of machine components to prevent future severe damages.